Investigation of revers-transcriptase polymerase chain reaction values of patients with COVID-19 findings in lung computed tomography results - Bolatli, Gunes; Tas, Fatih; Osman, OzÃ¼dogru (Jurnal Teknologi Laboratorium, 2020)
It turned out that the cause of pneumonia cases that occurred in China was due to SARS-CoV-2. The aim is to compare chest computer tomography and Revers-Transcriptase Polymerase Chain Reaction methods used in the diagnosis of COVID-19 disease with each other and to evaluate this disease with risk factors. The study was carried out on 66 patients. Epidemiological history, clinical symptoms, chest CT and RT-PCR results of the cases were examined. RT-PCR results of 1, 4, and 7 days were evaluated for each case with positive chest CT results. Thirty-seven of them were found to be positive on day 1, 5 of them were found to be positive on day 4, and 2 of them were found to be positive on day seven from 52 patients whose RT-PCR results were examined. In the remaining 8 cases, no positive findings were found. The most common findings are; cough (78.8%), fever (55.8%), and shortness of breath (28.8%). It was observed that 51.9% of the cases had chronic disease history and 50% of the patients using cigarettes had bilateral lung involvement in their CT results. Seven cases received intensive care support, 3 cases were intubated. Two of the intubated cases were exitus (3,8%). The positive results of RT-PCR were found to be negative in most of the cases which have positive chest CT; suggests that chest CT is more reliable in making a diagnosis. Therefore, evaluating chest CT results with RT-PCR can be an appropriate alternative approach in the diagnosis and treatment of disease. However, in order to be fully diagnosed, the patient's history, chronic diseases, age, symptoms, imaging, blood, and test findings must all be considered as a whole.